Diagnostic Accuracy of Salivary aMMP-8 Test in Infertile Women and Blood Finding Analysis - Lada Šumilin; Larisa Musić; Ivan Puhar; Ivan Sabol; Ivana Japirko; Krunoslav Kuna; Božana Lončar Brzak (University of Zagreb. School of Dental Medicine, 2022)
Introduction: The literature reviewed in this paper suggests that infertile patients present worse periodontal status, which may be causative to conception complications. This study aimed to validate an aMMP-8 point-of-care mouth rinse test in the population of women with unexplained infertility and compare it to age-matched fertile women with and without periodontitis. Furthermore, blood sampled inflammatory parameters were analyzed and compared between the two groups. It was hypothesized that the infertile women would present worse periodontal status and a greater number of positive aMMP-8 tests than fertile women, and they would have increased inflammatory blood parameters. Material and methods: The study included 50 healthy norm-ovulatory females aged 25-45 years with strictly defined unexplained (idiopathic) infertility, and 50 healthy norm-ovulatory women of the same age who had conceived and delivered naturally. Results: The sensitivity and specificity of the test for detecting periodontitis was 84% and 72% in the group of infertile patients, 88% and 68% in the group of fertile patients and 86% and 70% in the overall patient population. Infertile patients with periodontitis had less advanced periodontitis than the control group although this difference was not statistically significant. Blood inflammatory markers were significantly higher in infertile than in fertile women. Conclusion: This study has shown that infertile patients had better periodontal status and less advanced periodontitis than fertile women of the same age. Therefore, when interpreting the results of aMMP-8 tests for diagnosis of periodontitis, one should keep in mind the periodontal status of the examined population.